SOILS AND GEOAMBIENTS OF AMAZON CAMPINARANAS: GENETIC RELATIONSHIP BETWEEN GEOENVIRONMENTS AND LANDSCAPE EVOLUTION IN A TRANSECT IN THE UPPER RIO NEGRO BASIN, AMAZONIA - Oliveira Mendes, Debora de Sena; Bueno, Guilherme Taitson; Guimaraes, Felipe Silva; Rossin, Bruna Gomes [UNESP]; Nascimento, Nadia Regina do [UNESP] (Uniao Geomorfologia Brasileira, 2017)
The upper Rio Negro basin's Amazon Campinaranas are natural ecosystems which have sandy material as substrate, mainly Spodosols. These ecosystems occur in different topographical positions, as well as depressed areas on tableland interfluves, downslopes, alluvial terraces and paleochannels. Campinaranas are often surrounded by terra firme forests, being differentiated from the latter by vegetation size. There are important physiognomic variations, which are directly related to soil conditions (texture, nutrient content and organic matter), topography, and the influence of the water table level. Although occupying significant areas of the Rio Negro basin and constituting very fragile environments, there are few studies about the Campinaranas ecology in this region. The goal of this study is to characterize an area of campinaranas the upper Rio Negro basin's Amazon as well as the genetic relationships between soil and vegetation on the landscape scale. In the field a transect was made covering four different geoenvironments. In each of them, were performed soil analysis of sortive complex, organic matter content, nitrogen and texture. The Campinaranas floristic, structural, and diversity patterns are strongly related to the water table's depth, variation in soil texture and in the macro and micronutrient contentThe results indicate that the vegetation diversity and soils along the transect are closely linked to the development and evolution of podzolization and to the process of installation and incision of the drainage network in the area. It is concluded that the vegetation and its spacial variation has been an important indicator of the transformation.